Dimensionering av industrilager för biobränsle - Nilsson, Simon (2008)
The aim of this study was to develop a simple model for calculating stock costs for bio fuel at Billerud Karlsborg and subsequently recommending a suitable stock level of bio fuel. The stock components considered in the model are GROT (branches and tops), bark, dry wood chips, raw wood chips from barking and sawdust. The calculations are based on a probability distribution of historical deviations between ordered and delivered volumes. The model presents two different ways to manage the supply in case of irregular deliveries. The first way is to stock enough volume to cover the deviations and the second way is to compensate with a quick purchase from the spot market (at extra high purchase prices). In some situations the best solution might be a combination of these two alternatives. The stock model is used to support such decisions concerning dimensioning of stock levels.